DIAGNOSIS AND MANAGEMENT OF HYPEREMESIS GRAVIDARUM - Widayana, Ary; Megadhana, I Wayan; Putera Kemara, Ketut (E-Jurnal Medika Udayana; vol 2 no4 (2013):e-jurnal medika udayana)
Hyperemesis gravidarum is excessive nausea and vomiting in pregnant women to interfere with everyday activities because of poor patient's general condition due to dehydration. Studies estimate that nausea and vomiting occurred in 50-90% of pregnancies. Nausea and vomiting occurred in 60-80% of primi gravida and 40-60% of multi gravida. The cause of hyperemesis gravidarum is not known. Hyperemesis gravidarum, according to the severity of symptoms can be divided into three levels. The diagnosis of hyperemesis gravidarum is made through history, physical examination, and laboratory and USG finding. In patients with hyperemesis gravidarum levels II and III must be hospitalization with the provision of medical treatment, nutrition, parenteral fluids, and alternatives medicine. With a good treatment, the prognosis of hyperemesis gravidarum will be satisfying.
Keywords: diagnosis, management, hyperemesis gravidarum